Optimization of glass fiber reinforced polymer composite using response surface methodology for application on train panels - Yuni Hermawan; I Gusti Ketut Puja; Hendry Y. Nanlohy (Universitas Muhammadiyah Magelang, 2025)
Advancements in science and technology are creating challenges for conventional materials such as metals, often struggle to meet the demands of modern industry. In response to the issue, train industry has begun developing applications of Glass Fiber Reinforced Polymer (GFRP) composite for interior panels. Therefore, this research aimed to determine the impact of fiber volume fraction and arrangement direction on tensile as well as bending tests. This research also aimed to identify variations in composite manufacturing process parameters to achieve optimal tensile and bending strength values. The research methodology was an experimental procedure with data analysis using Statistics Software. During the analysis, the results showed that the fiber volume fraction of 30% with the fiber arrangement direction of 0° produced optimal tensile and bending strength values. Tensile and bending tests produced results of 100.82 kg/mm2 and 102.27 kg/mm2, respectively. A high fiber volume fraction led to optimal tensile and bending strength values because the fiber served as the main reinforcement. Additionally, direction of the fiber arrangement played a significant role, with 0° fiber orientation producing better results due to a more even fiber distribution compared to 90° direction. The results of this research could be applied to the wall panels in the railway industry.